Überbau Produktionsverhältnisse der Architektur im Anthropozän - Förster, Kim (2021)
Where do the raw materials for the large-scale and process-promissing architectural and infrastructural projects in steel and concrete come from? How is architecture entangled with the global system of supply chains? Who benefits from the distribution of property? What are the working conditions on major European construction sites? And in German architectural offices? How is architecture produced today? The publication deals with environmental destruction and land grabbing by the cement industry in Indonesia and Vietnam, the methods of the sand mafia on the Mekong, and the extraction of lithium in Bolivia for the batteries of our smart cities. It sheds light on structural inequalities in land policy and the precarious employment conditions of those who make architecture, who are usually forgotten in the contemplation of spectacular new buildings. In this way, the forms of architectural governmentality become tangible.